First order melting transitions of highly ordered dipalmitoyl phosphatidylcholine gel phase membranes in molecular dynamics simulations with atomistic detail - Schubert, Thomas; Schneck, Emanuel; Tanaka, Motomu (The journal of chemical physics, 2011)
Molecular dynamics simulations with atomistic detail of the gel phase and melting transitions of dipalmitoyl phosphatidylcholine bilayers in water reveal the dependency of many thermodynamic and structural parameters on the initial system ordering. We quantitatively compare different methods to create a gel phase system and we observe that a very high ordering of the gel phase starting system is necessary to observe behavior which reproduces experimental data. We performed heating scans with speeds down to 0.5 K/ns and could observe sharp first order phase transitions. Also, we investigated the transition enthalpy as the natural intrinsic parameter of first order phase transitions, and obtained a quantitative match with experimental values. Furthermore, we performed systematic investigations of the statistical distribution and heating rate dependency of the microscopic phase transition temperature.